Effects of vitamin D supplementation on plasma aldosterone and renin: a randomized placebo-controlled trial - Grübler, Martin R.; März, Winfried (The journal of clinical hypertension, 2016)
Increasing evidence describes a possible interplay between vitamin D insufficiency with increased aldosterone. The authors sought to evaluate the effect of vitamin D supplementation on plasma aldosterone concentration (PAC) in patients with hypertension and 25-hydroxyvitamin D[25(OH)D] insufficiency. The Styrian Vitamin D Hypertension Trial was a single-center, double-blind, placebo-controlled randomized clinical trial conducted from 2011 to 2014. Two hundred patients with arterial hypertension and 25(OH)D levels <30 ng/mL were enrolled. Study participants were randomized to receive either 2800 IU of vitamin D3 or placebo. The present investigation is a post hoc analysis using analysis of covariance adjusting for baseline differences. A total of 188 participants (mean±standard deviation age, 60.1±11.3 years; 47% women; 25(OH)D, 21.2±5.6 ng/mL) completed the trial. Mean differences between baseline and follow-up PAC in the control and intervention arm were +3.3 ng/dL and +0.9 ng/dL, respectively (P=.04). The findings indicate that vitamin D3 supplementation significantly decreases PAC in patients with arterial hypertension and 25(OH)D insufficiency.